Identification of a Schistosoma japonicum MicroRNA That Suppresses Hepatoma Cell Growth and Migration by Targeting Host FZD4 Gene - Jiang, Pengyue; Wang, Jing; Zhu, Shanli; Hu, Chao; Lin, Yu; Pan, Weiqing (Frontiers in Cellular and Infection Microbiology, 2022)
Previous studies have demonstrated miRNAs derived from plant and parasite can modulate mammalian gene expression and cell phenotype in a cross-kingdom manner, leading to occurrence of diseases or strengthening resistance of host to diseases such as cancer. In this study, we identified a schistosome miRNA (named Sja-miR-71a) through screening of 57 Schistosoma japonicum miRNAs that exerts antitumor activity in vitro and in vivo models. We demonstrated presence of this parasite miRNA in liver cell during infection. We showed that Sja-miR-71a arrested cell cycle at G0/G1 phase of hepatoma cell lines and inhibited cell proliferation in vitro. The HepG2 transfected with Sja-miR-71a mimics displayed significant reduction of migration and colony formation. Further, growth of the tumor cells transfected with the Sja-miR-71a mimics was obviously suppressed in a xenograft mouse model. Mechanically, we found the antitumor activity of Sja-miR-71a was through targeting a host gene encoding Frizzled Class Receptor 4 (FZD4), as FZD4 small interfering RNAs (siRNAs) generated a similar inhibitory effect on the tumor. These data indicated that Sja-miR-71a is a tumor suppressor miRNA and suggested this parasite-derived miRNA as a potential therapeutic target for cancer.